Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) \(4x^2-y^2+4x+1\)
\(=\left(4x^2+4x+1\right)-y^2\)
\(=\left(2x+1\right)^2-y^2\)
\(=\left(2x+y+1\right)\left(2x-y+1\right)\)
16x - 5x² - 3 = -5x² + 16x - 3 = -5x² + 15x + x - 3
= -5x(x - 3) + (x - 3) = (x - 3)(1 - 5x)
Câu b sorry nha
a, A =x4 - ( x2 - 2x + 1)
= x4 - ( x - 1)2
= (x2 - x + 1) ( x2 + x - 1)
a,x4-4x3+8x2-16x+16
=x4-4x3+4x2+4x2-16x+16
=x2.(x-2)2+4.(x-2)2
=(x-2)2(x2+4)
a,X^3-16x =x(x^2-16)
b,y(y-2)-3(y-2)=(y+3).(y-2)
c,x^2+4x+4-y^2=(x+2)^2-y^2=(x+y+2).(x+2-Y)
D,4^2y^3-12x^2y^4+16X^5y^3=4x^2y^2(y-3y^2+4X^3y)
\(16x^2+y^2+4y-16x-8xy\)
\(=\left(4x-y\right)^2-4\left(4x-y\right)\)
\(=\left(4x-y\right)\left(4x-y-4\right)\)
a) \(16x^2+y^2+4y-16x-8xy\)
\(=\left(4x\right)^2-8xy+y^2+4\left(y-4x\right)\)
\(=\left(4x-y\right)^2+4\left(y-4x\right)\)
\(=\left(y-4x\right)^2+4\left(y-4x\right)=\left(y-4x\right)\left(y-4x+4\right)\)
\(-5x^2+16x-3\)
\(=-5x^2+15x+x-3\)
\(=-5x\left(x-3\right)+\left(x-3\right)\)
\(=\left(x-3\right)\left(1-5x\right)\)
16x - 5x^2 - 3
=x - 5x^2 + 15x - 3
=x(1-5x) + 3(5x-1)
=3(5x-1) -x(5x-1)
=(3-x)(5x-1)
= 4y.( 4x3 + 1/24z3)